2004
DOI: 10.1158/1078-0432.ccr-04-0165
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Chromosomal Alterations in Breast Ductal Carcinoma In situ

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
105
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 34 publications
14
105
0
2
Order By: Relevance
“…Comparative genomic hybridization analysis of breast DCIS and IDC found no significant difference in the number of chromosomal abnormalities, although the frequency of a few specific changes varied in high grade versus low grade DCIS and between DCIS and concurrent IDC. 9 A more recent study confirmed that DCIS is genetically advanced. Allelic imbalance of 52 microsatellite markers of chromosomal regions commonly lost in breast cancer increased significantly between atypical ductal hyperplasia and DCIS but not between DCIS and IDC.…”
mentioning
confidence: 95%
“…Comparative genomic hybridization analysis of breast DCIS and IDC found no significant difference in the number of chromosomal abnormalities, although the frequency of a few specific changes varied in high grade versus low grade DCIS and between DCIS and concurrent IDC. 9 A more recent study confirmed that DCIS is genetically advanced. Allelic imbalance of 52 microsatellite markers of chromosomal regions commonly lost in breast cancer increased significantly between atypical ductal hyperplasia and DCIS but not between DCIS and IDC.…”
mentioning
confidence: 95%
“…DCIS has long been known to be heterogeneous in its morphologic features, presentation, and clinical behavior. The emergence of genomic and gene expression profiling has established that DCIS is heterogeneous at a level of molecular complexity that is comparable with or perhaps greater than that of invasive disease (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Although certainly less studied, the heterogeneity observed in the microenvironment surrounding individual premalignant lesions may also be a critical determinant of their future behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) also shows frequent losses of distal 8p in breast, colorectal, prostate, bladder and other cancers (e.g. Davidson et al, 2000;AbdelRahman et al, 2001;Karan et al, 2003;Hurst et al, 2004;Hwang et al, 2004), and more recently array CGH has begun to provide more detail of these losses (e.g. Paris et al, 2003;Douglas et al, 2004;Hurst et al, 2004;Nakao et al, 2004;Garcia et al, 2005).…”
Section: Introductionmentioning
confidence: 99%